Socio-economic inequalities in tobacco-related diseases in Portugal: an ecological approach. (January 2016) - Alves, J.; Nunes, C.; Perelman, J.
Abstract: Objectives: The existence of socio-economic (SE) inequalities in smoking is well demonstrated, but less is known about its consequences. This study measures SE inequalities in the prevalence of tobacco-related diseases (TRD) in Portugal, using a new area-based SE indicator. Study design: Ecological study. Methods: In-patient data were used to identify TRD discharges at all Portuguese NHS hospitals for the year 2011. The definition of TRD incorporates malignant cancers, cardiovascular diseases, cerebrovascular diseases and respiratory diseases. We created an area-based SE indicator on the basis of census data, using factor analyses. The association between the prevalence of TRD and the SE indicators was measured using Generalized Linear Models. The spatial correlation of this indicator was assessed using variograms. Results: Two area-based SE factors were identified at the parish level, reflecting (i) social position (education and occupation); and (ii) deprivation (overcrowding and manual occupations). Upper-social-class areas were associated with a lower prevalence of malignant cancers, cardiovascular, and respiratory diseases. Conclusion: We found significant inequalities in TRDs across Portuguese parishes using a newly created area-based SE indicator reflecting several SE dimensions. This result emphasizes that inequalities in smoking are reflected in inequalities in health, and should be tackled through equality-oriented area-based tobacco policies. Highlights: There is no consistent evidence about inequalities in tobacco-related diseases (TRD). A new area-based socio-economic indicator was created for Portugal. We found significant area-based inequalities in TRDs. A lower prevalence rate of TRD was associated to more privileged areas.